Prevention of Vascular Anastomotic Stenosis With 2-Octylcyanoacrylate. Issue 1 (January 2019) - Liang, Xiangdang; Liu, Shen; Fang, Zhuoqun; Sun, Geng; Guo, Zhanshe
Abstract : Abstract: Although conventional microvascular anastomoses are well-studied, postoperative anastomotic stenoses remain a common surgical complication. The use of 2-octylcyanoacrylate to stabilize vascular anastomoses using a rabbit anastomosis model was investigated. A carotid artery anastomosis model was established in 20 New Zealand rabbits (2.5–3.0 kg): 10 underwent conventional anastomosis surgery with sutures only, while 10 underwent suture ligation, followed by the application of 2-octylcyanoacrylate. Vascular patency and pulse strength were observed after adhesive solidification. The artery diameter was measured preoperatively and at 5 minutes, 2 weeks, and 4 weeks postoperatively. An angiography was performed at 4 weeks postoperatively. Hyperplasia and the induced nitric oxide synthase (iNOS) content of the intima and media layers from the anastomotic stoma were assessed using immunohistochemistry. The artery inner diameter of experimental group decreased at each time point postoperatively (1.686 ± 0.066 cm; 1.656 ± 0.069 cm; 1.646 ± 0.074 cm) ( P ⩽ 0.01). At 4 weeks postoperatively, the intima and the media around the anastomosis was both significantly thinner in the experimental group (13.21 ± 0.84 μm; 234.86 ± 13.84 μm) than in the control group (17.06 ± 0.96 μm; 279.88 ± 34.22 μm) ( P < 0.05). At 4 weeks postsurgery, intravascular iNOS expression was increased in both groups but was higher in the experimental group (82.5% versus 47.5%). The above results indicated that 2-octylcyanoacrylate adhesive can inhibit stenosis of vascular anastomoses.